Pendidikan Akhlak dalam Konsep Tazkiyatun Nafs Perspektif Imam Al-Ghazali dan Relevansinya terhadap Degradasi Moral Generasi Muda - Bayhaqi, Hasmi Nur; Masnawati, Eli (ALSYS, 2024)
Today's rapid and sophisticated technological advances have created problems. Without being accompanied by moral fortification from the school or family, it can have a negative impact on students. Moral degradation is currently an increasingly worrying problem, including in Indonesia, which is caused by the negative influence of western culture and thought patterns, which are normalized by information technology and lead to various actions that are contrary to religion and even criminal in nature. Various phenomena related to the decline in ethics in society, especially juvenile delinquency, are proof that moral education needs to be strengthened in education system. Tazkiyyatun nafs purification of the soul taught by Imam Al Ghazali is a very rich and comprehensive concept of moral education. The aim of this research is to find out and analyze how moral education is in the concept of tazkiyatun nafs from AL-Ghazali's perspective, as well as the relevance of moral education from tazkiyatun nafs from Al-Ghazali's perspective in overcoming the moral decline of today's young generation. A qualitative approach was used in this research to obtain in-depth results through literature study. The results show that Imam Al-Ghazali developed the concept of tazkiyatun nafs, which means purification of the soul through cleansing oneself of despicable traits and replacing them with habituation to praiseworthy traits. Apart from that, Al-Ghazali's thoughts are a reference in dealing with current educational problems, where students' behavior often does not reflect moral values. By integrating the concept of tazkiyatun nafs, the education system can form a generation that has faith, noble character and piety, according to what Al-Ghazali emphasized regarding the importance of forming moral character through education which is actualized through habituation and example.